Bibliometric and authorship trends over a 30 year publication history in two representative US sports medicine journals. Issue 3 (March 2020) - Dynako, Joseph; Owens, Garrett W.; Loder, Randall T.; Frimpong, Tony; Gerena, Rolando Gabriel; Hasnain, Fawaz; Snyder, Dayton; Freiman, Serena; Hart, Kyle; Kacena, Melissa A.; Whipple, Elizabeth C.
Abstract: Bibliometric studies are important to understand changes and improvement opportunities in academia. This study compared bibliometric trends for two major sports medicine/arthroscopy journals, the American Journal of Sports Medicine® ( AJSM® ) and Arthroscopy® over the past 30 years. Trends over time and comparisons between both journals were noted for common bibliometric variables (number of authors, references, pages, citations, and corresponding author position) as well as author gender and continental origin. Appropriate statistical analyses were performed. A p < 0.001 was considered statistically significant. One representative year per decade was used. There were 814 manuscripts from AJSM® and 650 from Arthroscopy® . For AJSM® the number of manuscripts steadily increased from 86 in 1986 to 350 in 2016; for Arthroscopy® the number of manuscripts increased from 73 in 1985/1986, to 267 in 2006, but then dropped to 229 in 2016. There were significant increases in all bibliometric variables, except for the number of citations which decreased in Arthroscopy® . There were significant differences in manuscript region of origin by journal (p = 0.000002) . Arthroscopy® had a greater percentage of manuscripts from Asia than AJSM® (19.3% vs 11.5%) while AJSM® had a greater percentage from North America (70.3% vs 59.2%); both journals had similar percentages from Europe (18.2% for AJSM® and 21.6% for Arthroscopy® ). For AJSM® the average percentage of female first authors was 13.3%, increasing from 4.7% in 1986 to 19.3% in 2016; the average percentage of female corresponding authors was 7.3%. For Arthroscopy®, the average percentage of female first authors was 8.1%, increasing from 2.8% in 1985/1986 to 15.7% in 2016 (p = 0.00007). In conclusion, AJSM® and Arthroscopy® showed an increase in most variables analyzed. Although Arthroscopy® is climbing at a higher rate than AJSM® for female authors, AJSM® has an overall greater percentage of female authors. Abstract : Bibliometric, Sports medicine, Author, Gender, Geographic region, AJSM®, Arthroscopy®, Biological sciences; Bioinformatics; Health sciences; Musculoskeletal system; Social sciences; Information science.